Analisis Efektivitas Retribusi terhadap Pendapatan Asli Daerah di Kabupaten Maros - Nurjaya, Muhammad (Journal of Government Insight, 2023)
This study aims to determine and analyze the effectiveness of retribution on regional original income in Maros Regency. The data used in this study are secondary data, research data obtained through intermediary media or indirectly in the form of books, records of the annual financial reports of the regional revenue service office (DISPENDA). The analytical method in this study uses simple linear regression analysis, to determine the effect of the independent variable, namely retribution (x) on the dependent variable, namely local revenue (y). Correlation coefficient to determine whether or not the linear relationship between variables is strong, Determination coefficient to determine the strength of the independent variable, namely retribution (x) on the dependent variable, namely regional original income (y). The results of the study found that the magnitude of the influence of the independent variable, namely retribution (x) on the dependent variable, namely the original income of blood (y), was 50.9 or 50.9%.